Analisis Perbandingan Pendapatan Tukang Ojek Online dan Tukang Ojek Konvensional di Kota Banjarmasin - Habibie, Muhammad Rifqi (PPJP ULM, 2018)
The purpose of this study is to find out more excellent where is the incomebetween online motorcycle taxi drivers with conventional motorcycle taxi drivers inthe city of Banjarmasin.The method of analysis used is descriptive quantitative. Types and sources ofdata primary data obtained through questionnaires and direct interviews with onlinemotorcycle taxi drivers and conventional motorcycle taxis.The results of the research can be obtained analysis that the income ofmotorcycle taxis online is higher than the payment of conventional motorcycle taxidrivers in the city of Banjarmasin.